KEABSAHAN PERINTAH LISAN ATAS PENGHILANGAN WAKTU ISTIRAHAT MINGGUAN DAN UPAH LEMBUR - Asri Wijayanti; Aldiansah Pratama (Trunojoyo Madura University, 2022)
Overtime pays and work agreements between workers and outsourcing companies are often not enforceable. This study aims to determine the form of legal protection for overtime wages in outsourcing companies and their legal remedies. This research is normative juridical, especially on legal systematics and the level of legal synchronization. The results showed that there must be overtime orders and worker approvals. Overtime work is given after working more than 40 hours/week, a maximum of 4 hours/day and 18 hours/week. Employers are required to provide adequate rest time and minimum consumption of 1400 kilo calories. Guarantees for overtime pay are difficult to apply to outsourcing companies because work orders are given by employers to workers, not based on contracts that workers have made with outsourcing companies.. The legal remedy that can be taken by workers who do not receive overtime pay at the outsourcing company is to conduct bipartite negotiations with the entrepreneur who runs the outsourcing company. If it fails, you can apply for mediation; the lawsuit will be submitted to the Industrial Relations Court.